ERK 1/2 activation does not contribute to increased survival mediated by bone marrow cells after 90% partial hepatectomy in Wistar rats - Ochs de Muñoz, Gustavo Alfredo; Kretzmann, Nelson Alexandre; López, Mónica Luján; Kieling, Carlos Oscar; Uribe-Cruz, Carolina; da Silva, Luciano Basso; Osvaldt, Alessandro Bersch; Matte, Ursula da Silveira (Clinical and Biomedical Research, 2017)
We investigated the influence of bone marrow cells upon activation of ERK ½ in an animal model of 90% PH. Phosphorylated ERK 1/2 was evaluated by western blot. No differences were found between the groups. Thus, increased survival does not appear to be mediated by ERK 1/2 activation. Keywords: MAP Kinase Signaling System; stem cells; acute liver failure